The Effect of Wearing A Mask on Oxygen Saturation and Pulse Rate During Climbing Stair in Public Areas - Jaya, I Putu Prisa; Astrawan, I Putu; Negara, Ni Luh Gede Aris Maytadewi; Empuaji, Made Ganggas Dwiatmaja (GLOBAL HEALTH SCIENCE GROUP, 2024)
The wearing of masks is one of the mitigation strategies in preventing transmission and is the main protective tool in the Covid-19 pandemic. The wearing of masks for a long duration and long period of time influences the respiratory, vision, and communication systems. Purpose: The purpose of this study was to determine the effect of wearing a mask on climbing stairs on physiological responses measured through oxygen saturation and pulse rate. Method: Experimental research with crossover design. The research was conducted at the Bali International University in June – August 2022. The research subjects in this study were employees and lecturers for 40 people. Results: Based on the results of the analysis with the t-independent test, there was a significant difference in oxygen saturation and pulse rate between the two groups. The same result was also obtained in period II, there was a difference in oxygen saturation and pulse rate between the two groups meaningfully, with a range of values that were not much different from the results in the activity of climbing the ladder of period I. Overall, there was a significant difference in oxygen saturation and pulse rate between wearing a mask and not wearing a mask. Conclusion: Based on the results of this study, it has a high impact on physiological response, so the elderly is not recommended to use masks when climbing stairs that exceed 2 floors.